Analysis of the occurrence of taurodontism in patients attending the Tygerberg Oral Health Centre - Benzahya, Mohamed (University of the Western Cape, 2016)
Magister Scientiae Dentium - MSc(Dent) === Aim: Analysis of the occurrence of taurodont molars among patients attending the Tygerberg Oral Health Centre. Methodology: A retrospective descriptive study comprising 1608 panoramic radiographs of patient records, 815 females and 793 males, ranging in ages from 18 to 68 years old. The panoramic radiographs were evaluated for presence of taurodontism. Gender predilection and location of taurodont molars were analysed using a chi-square test. Results: Taurodontism was found in 52 (3.23%) radiographs distributed according to gender (30 females and 22 males [P > 0.05]). The overall prevalence of taurodont molars was (0.73%) from a total of 17148 molars that were examined. The mandibular molar teeth were more affected than the maxillary molar teeth and the second mandibular tooth was the most affected. Conclusion: Taurodontism was not uncommon in a group of patients that attended the Tygerberg Oral Health Centre, UWC. Further larger scale studies are required to assess its distribution in the general population of South Africa to compare it with other ethnic groups and to establish any associations. However, taurodontism in mandibular teeth is a condition that should be taken into consideration, especially the second mandibular tooth, to avoid complications.